2017
DOI: 10.1093/jhered/esx080
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Signatures of Sexual Conflict

Abstract: Sexual conflict is a specific class of intergenomic conflict that describes the reciprocal sex-specific fitness costs generated by antagonistic reproductive interactions. The potential for sexual conflict is an inherent property of having a shared genome between the sexes and, therefore, is an extreme form of an environment-dependent fitness effect. In this way, many of the predictions from environment-dependent selection can be used to formulate expected patterns of genome evolution under sexual conflict. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 109 publications
5
50
0
Order By: Relevance
“…This bias in genetic variation suggests that there may be differential selection (intralocus sexual conflict) between males and females for autosomal or pseudoautosomal regions (segments of sex chromosomes that recombine) in the deacon rockfish genome. Adaptive genetic differences can occur between the sexes if males and females are placed under different selection pressures for traits such as reproduction and behavior (Bonduriansky & Chenoweth, ; Cox & Calsbeek, ; Kasimatis, Nelson, & Phillips, ). The genetic basis for such traits can be attributed to variation at a single locus (Bonduriansky & Chenoweth, ; Bonduriansky, Maklakov, Zajitschek, & Brooks, ; Cox & Calsbeek, ; Kasimatis et al, ; Mank, ; Parker & Partridge, ; Rowe, Chenoweth, & Agrawal, ), which can lead to high estimates of F ST (Flanagan & Jones, ; Lucotte, Laurent, Heyer, Ségurel, & Toupance, ), as observed in this study (Table C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This bias in genetic variation suggests that there may be differential selection (intralocus sexual conflict) between males and females for autosomal or pseudoautosomal regions (segments of sex chromosomes that recombine) in the deacon rockfish genome. Adaptive genetic differences can occur between the sexes if males and females are placed under different selection pressures for traits such as reproduction and behavior (Bonduriansky & Chenoweth, ; Cox & Calsbeek, ; Kasimatis, Nelson, & Phillips, ). The genetic basis for such traits can be attributed to variation at a single locus (Bonduriansky & Chenoweth, ; Bonduriansky, Maklakov, Zajitschek, & Brooks, ; Cox & Calsbeek, ; Kasimatis et al, ; Mank, ; Parker & Partridge, ; Rowe, Chenoweth, & Agrawal, ), which can lead to high estimates of F ST (Flanagan & Jones, ; Lucotte, Laurent, Heyer, Ségurel, & Toupance, ), as observed in this study (Table C).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive genetic differences can occur between the sexes if males and females are placed under different selection pressures for traits such as reproduction and behavior (Bonduriansky & Chenoweth, ; Cox & Calsbeek, ; Kasimatis, Nelson, & Phillips, ). The genetic basis for such traits can be attributed to variation at a single locus (Bonduriansky & Chenoweth, ; Bonduriansky, Maklakov, Zajitschek, & Brooks, ; Cox & Calsbeek, ; Kasimatis et al, ; Mank, ; Parker & Partridge, ; Rowe, Chenoweth, & Agrawal, ), which can lead to high estimates of F ST (Flanagan & Jones, ; Lucotte, Laurent, Heyer, Ségurel, & Toupance, ), as observed in this study (Table C). A recent RAD sequencing study of gulf pipefish Syngnathus scovelli (Evermann & Kendall, 1896) found that males typically possessed the minor allele, whereas females had the major (Flanagan & Jones, ), which is the same pattern observed for most of the 92 deacon rockfish outlier loci in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work in no way challenges the notion that SAS could be widespread across the genome. However, the above and previous (Kasimatis, Nelson, & Phillipps, 2017) theoretical considerations indicate that intersex differentiation maintained by continuous sexually antagonistic viability selection within a population should be subtle in magnitude.…”
Section: Analytical Implicationsmentioning
confidence: 90%
“…While the maintenance of polymorphism may have been a primary motivation for previous work, a goal of modern genomics is to use specific signals of genomic differentiation to identify the loci underlying sexually antagonistic genetic effects (Mank 2017a). Building on our previous work (Kasimatis et al 2017) allowed us to consider the expected degree of between-sex divergence both when an antagonistic polymorphism is maintained at equilibrium in the population, and when no such stable equilibrium exists, so one of the two alleles sweeps towards fixation to the detriment of one sex. Our model and accompanying simulations highlight several potential limitations of detecting sex-specific differentiation in empirical studies.…”
Section: Discussionmentioning
confidence: 99%